ANALISIS PENGUJIAN ARUS BOCOR LINE POST INSULATOR 70 kV YANG TERKONTAMINASI POLUTAN INDUSTRI - Lanto Mohamad Kamil Amali (Foristek, 2012)
Failure of Insulators of ‘Line Post Insulator 70 kV type’ usually caused by many factors, such as the leakage current oncontaminated insulator surfaces. This leakage current will cause interference with the electrical energy distribution system. Thisstudy reported the results of testing the leakage current on insulator 70 kV Line Post Insulator type performed on high-voltagelaboratory Ujung Pandang State Polytecchnics. Based on testing, the maximum leakage current value obtained in wet conditions polluted with spraying of pollutants ESDD = 3.2 mg/cm2 and NSDD = 0.08 mg/cm2 with a value of leakage currentof 7.4 mA at an applied voltage of 22 kV, this can result in flashover.